Black Girl Thought in the Work of Ntozake Shange. Issue 2 (1st July 2019) - Keleta-Mae, Naila
Abstract : In this article I examine the performances of black girlhood in two texts by Ntozake Shange—the choreopoem "for colored girls who have considered suicide when the rainbow is enuf" (1977) and the novel Sassafras, Cypress and Indigo (1982). The black girls whom Shange portrays navigate anti-black racism in their communities, domestic violence in their homes, and explore their connections with spirit worlds. In both these works, Shange stages black girls who make decisions based on their understanding of the spheres of influence that their race, gender, and age afford them in an anti-black patriarchal world dominated by adults. I draw, too, from Patricia Hill Collins's work on feminist standpoint theory and black feminist thought to introduce the term black girl thought as a theoretical framework to offer insights into the complex lives of black girls who live in the post-civil rights era in the United States.